To perform partial fraction decomposition, start by factoring the denominator of the fraction, x^3 + 3x.
x^3 + 3x = x(x^2 + 3)
Since there are no repeated factors in the denominator, the partial fraction decomposition will have the following form:
x-3/(x^3+3x) = A/x + B/x^2 + C/(x^2 + 3)
To find the values of A, B, and C, multiply both sides of the equation by x^3 + 3x:
x-3 = A(x^2 + 3) + Bx(x^2 + 3) + Cx^3
Expanding and collecting like terms:
x-3 = Ax^2 + 3A + Bx^3 + 3Bx + Cx^3
Now, equating the coefficients of each term:
1x^3 = Bx^3 + Cx^3
1 = B + C
0x^2 = Ax^2
0 = A
1x = 3Bx
1 = 3B
B = 1/3
Substituting B into the equation 1 = B + C:
1 = 1/3 + C
C = 2/3
Therefore, the partial fraction decomposition of x-3/(x^3+3x) is:
x-3/(x^3+3x) = 0/x + 1/(3x^2) + 2/(3(x^2 + 3))
Partial fraction decomposition x-3/x^3+3x
1 answer